Protective effects of Sanguisorba minor and Ferulago angulata total extracts against beta-amyloid induced cytotoxicity and oxidative stress in cultured cerebellar granule neurons - Sholeh Akbari; Maliheh Soodi; Homa Hajimehdipoor; Nasim Ataei (Shahrekord University of Medical Sciences, 2019)
Introduction: Alzheimer's disease (AD) is an age-dependent neurodegenerative disorder and major cause of mortality in the elderly. AD has a complex pathophysiology and needs new multi-targeted compounds to halt the disease progression through several mechanisms. Medicinal plants contain various compounds with heterogeneous pharmacological effects, therefore are a good source. The aim of this study was to evaluate the protective effect of total extracts of Sanguisorba minor and Ferulago angulata on beta-amyloid (Aβ)-induced toxicity in primary neural cell culture.Methods: Cerebellar granule neurons (CGNs) were cultured according to standard protocols. The cultured neurons were incubated with Aβ alone or in combination with different concentrations of extracts for 24 hours. Cell viability was measured by methylthiazolyldiphenyl-tetrazolium (MTT) assay. In addition acetylcholinesterase (AChE) activity and oxidative stress markers were measured after incubation. Also, the effects of different concentrations of the extracts on AChE activity of the cultured neurons were investigated. For measuring the acute toxicity of the extract, LD50 was estimated by limit test.Results: Both extracts could protect CGNs against Aβ-induced cell death. Aβ-induced oxidative stress and increase of AChE activity were ameliorated by both extracts. S. minor extract dose-dependently reduced AChE activity in cultured CGNs. LD50 of both extracts was estimated above 2000 mg/kg and considered as safe.Conclusion: Both studied extracts protected CGNs against Aβ-induced toxicity by ameliorating oxidative stress mechanism. According to these results, these extracts are recommended for further investigation in AD treatment.